2009
DOI: 10.3912/ojin.vol14no03man05
|View full text |Cite
|
Sign up to set email alerts
|

More than Words: Promoting Health Literacy in Older Adults

Abstract: Inadequate health literacy disproportionately affects older adults in the United States. The complexities associated with managing chronic disease and the cognitive and sensory changes associated with aging compound the challenges of teaching this highly vulnerable group. In order to enhance comprehension and bring about positive health behavior changes, the nurse must use more than words when teaching an older adult. Multiple teaching strategies that are tailored to accommodate the cognitive, physical, and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…In line with current pretraining findings, prior research has shown that older adults have a decreased capacity to process multiple pieces of information (Stevens, 2003) and benefit from learning manageable chunks of information. Additionally, research involving medical adherence in older adults, suggests that patient education strategies should be tailored to account for age-related changes in cognitive functioning (Speros, 2009;Zhang, Swartzman, Petrella, Gill, & Minda, 2017). For example, key points should be reinforced, so that the patient will become familiarized with the information and complex information should be broken down into simpler points, as This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Implications For the Usefulness Of Pretraining In Category L...mentioning
confidence: 99%
“…In line with current pretraining findings, prior research has shown that older adults have a decreased capacity to process multiple pieces of information (Stevens, 2003) and benefit from learning manageable chunks of information. Additionally, research involving medical adherence in older adults, suggests that patient education strategies should be tailored to account for age-related changes in cognitive functioning (Speros, 2009;Zhang, Swartzman, Petrella, Gill, & Minda, 2017). For example, key points should be reinforced, so that the patient will become familiarized with the information and complex information should be broken down into simpler points, as This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Implications For the Usefulness Of Pretraining In Category L...mentioning
confidence: 99%
“…Vision changes and hearing loss may impede information processing, while decreased motor function may inhibit adoption of necessary health behaviors. The elderly may also experience trouble in higher-order thinking skills, such as comprehension, comparison and contrast, and reasoning ( Speros, 2009 ). In addition, age-cohort differences in health education during formal schooling contribute to disparities between age groups ( Ashida et al, 2011 ; Xie et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In research, the same information needs to be provided to allow participants who are consumer representatives to understand the research questions being asked 4 . This is particularly important when working with populations that may have limitations in their capacity to understand the complex information being conveyed, such as older adults 5 . The onus, then, lies with the researchers to use methods that communicate the context, background information, and research questions clearly and accurately.…”
Section: Introductionmentioning
confidence: 99%
“…being conveyed, such as older adults. 5 The onus, then, lies with the researchers to use methods that communicate the context, background information, and research questions clearly and accurately.…”
mentioning
confidence: 99%